Iot Based Health and Position Tracking System for Soldier Security System - arayudu, G.Sanjeev; Venkateswramma, B.; Devi, G.Rukmini; Gowthami, Alavalapati Veera (International Journal of Psychosocial Rehabilitation, 2025)
Nowadays all nations keep its security at high priority. Wars are being fought for land, water and acquiring the position of most powerful nation. A country’s arm forces consist of three professional uniformed services: the army, the navy, and the air force. Soldiers being the backbone of any armed force usually lose their lives due to lack of medical help when in emergency, also soldiers who are involved in missions or in special operations get straggled on war fields and lose contact with the authorities. The system consists of two units viz, Soldier’s unit and Base station unit. Soldier’s unit can be integrated to the soldier’s jacket as shown in below figure. Base station unit is major mobile. He/she can observe all parameters in their mobile. Further, this project is enhanced using IOT technology using NODE MCU. And indication at local set up is established by using LED bulb.